2011
DOI: 10.1515/dmdi.2011.101
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 and ABCG1 expressions are regulated by statins and ezetimibe in Caco-2 cells

Abstract: Our findings reveal that, at the concentrations studied, statins isolated or combined with ezetimibe, but not ezetimibe alone, downregulate ABCA1 mRNA expression in Caco-2 cells. Moreover, simvastatin combined with ezetimibe treatment also decrease the ABCG1 levels in these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
1
5
1
2
Order By: Relevance
“…Indeed, the most significantly associated gene was the LDLR , which was up-regulated among patients using statin. Of the strongly correlated genes, ABCG1 was down-regulated with statin use, in line with previous reports [ 45 ]. Furthermore, sterol-C4-methyl oxidase-like (SC4MOL) and 24-dehydrocholesterol reductase ( DHCR24 , also known as seladin 1) were significantly up-regulated among statin users.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the most significantly associated gene was the LDLR , which was up-regulated among patients using statin. Of the strongly correlated genes, ABCG1 was down-regulated with statin use, in line with previous reports [ 45 ]. Furthermore, sterol-C4-methyl oxidase-like (SC4MOL) and 24-dehydrocholesterol reductase ( DHCR24 , also known as seladin 1) were significantly up-regulated among statin users.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously demonstrated that statins increase the levels of the microRNA miR33, which downregulates the expression of ABCA1, decreases the ABCA1 efflux-capacity of treated cells, and counteracts the effect of dalcetrapib on cholesterol efflux in cultured macrophages [42]. In addition, simvastatin and atorvastatin treatments have been shown to decrease the level of ABCA1 mRNA in vitro and in circulating human blood cells [25,26]. In the present study, we observed a reduction in ABCA1 mRNA in the intestine of simvastatin-treated hamsters (see Supplementary Material) which was associated with a decrease in plasma and liver lutein and zeaxanthin levels.…”
Section: Discussionmentioning
confidence: 99%
“…We next characterized the response of hamsters to dietary lutein and zeaxanthin by measuring lutein and zeaxanthin plasma levels and liver accumulation in hamsters treated with the liver X receptor (LXR) agonist T0901317, which increases ABCA1 transcription and protein levels in most tissues including liver and intestine [24]. Since statins decrease ABCA1 expression in human intestinal Caco-2 cells [25] by cholesterol depletion, as well as decreasing oxysterol levels and increasing miR33 [26], we investigated the effect of simvastatin on plasma and liver lutein and zeaxanthin levels. The CETP modulator dalcetrapib enhances the activity of CETP, thus favoring lipid-poor apoA1 formation, whereas non-selective, complete CETP inhibitors such as anacetrapib blunt this process [23].…”
Section: Introductionmentioning
confidence: 99%
“…Estes dados estão apresentados como Apêndice 1 e foram publicados em artigos de nosso grupo de pesquisa (RODRIGUES et al, 2009a;RODRIGUES et al, 2009b;GENVIGIR et al, 2010;CERDA et al, 2011;GENVIGIR et al, 2011). …”
Section: Estudos In Vitrounclassified